Catalyst, preparation method and application of catalyst in preparation of hydrogen-rich fuel gas through biomass steam gasification
By using a catalyst with a core-shell structure, the problem of large amount of tar in the preparation of hydrogen-rich gas by the existing catalysts in the preparation of hydrogen-rich gas by water vaporization of biomass is solved, efficient catalytic tar cracking and improving hydrogen production, and improving the stability of the catalyst.
Patent Information
- Application Number
- CN202411830255.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-21
AI Technical Summary
The existing catalysts have a large amount of tar in the preparation of hydrogen-rich gas for biomass water vapor vaporization, which affects the gasification efficiency and hydrogen yield, and the stability and performance of the catalyst are insufficient.
A catalyst with a core-shell structure is used, which consists of iron oxide as a core body and silica microspheres as a core-shell. The iron oxide is coated through the in-situ growth of silica microspheres to form a mesoporous catalyst.
This catalyst can effectively catalyze tar cracking, improve the volume content of hydrogen in the preparation of hydrogen-rich gas by water vaporization of biomass, and at the same time improve the stability and service life of the catalyst.
Smart Images

Figure CN119657140A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of biomass energy utilization, and specifically, to a catalyst, a preparation method, and an application thereof in the preparation of hydrogen-rich fuel gas by steam gasification of biomass. Background Art
[0002] The research and development and application of biomass energy will help alleviate the global energy shortage, meet the requirements of the common utilization of multiple energy sources for sustainable development, improve the energy structure, rationally utilize resources, and protect the country's energy security. Biomass pine wood pellet fuel uses wood waste and belongs to the resource recycling industry. With the development and progress of science and technology, biomass energy can be efficiently utilized through various conversion technologies to produce various clean fuels and electricity to replace mineral fuels such as coal, oil and natural gas. Thermochemical conversion technologies in the utilization of biomass energy mainly include gasification technology, pyrolysis technology, etc., the purpose is to convert biomass energy into thermal energy. Biomass gasification technology has been more widely studied and applied due to its relatively high conversion rate. Biomass is converted into high-quality hydrogen-rich synthesis gas through thermochemical reactions. The main components include CH4, CO, H2, etc. Among them, hydrogen has higher value due to its higher calorific value and clean combustion products.
[0003] Biomass gasification is considered the fastest and most economical method for producing H2, but tar is produced in the process, which seriously affects the gasification efficiency and hydrogen yield, and also damages the equipment. Although the amount of tar can be reduced by introducing a catalyst that can assist in cracking tar into the system, a single-performance catalyst is not ideal in terms of increasing the yield of hydrogen-rich components in the fuel gas and maintaining catalyst stability during use.
[0004] Therefore, the current catalysts, preparation methods and their applications in the preparation of hydrogen-rich fuel gas by steam gasification of biomass still need to be improved. Summary of the invention
[0005] The present application aims to provide a catalyst and a preparation method thereof to solve or alleviate one or more technical problems in the related art.
[0006] In one aspect of the present application, a catalyst is provided. The catalyst has a core-shell structure, and the core-shell structure includes: a core body, the core body contains iron oxide; a core shell, the core shell covers at least part of the surface of the core body, and the core shell contains silicon dioxide microspheres. The catalyst has the function of catalyzing tar cracking and increasing the volume content of hydrogen in the preparation of hydrogen-rich fuel gas by steam gasification of biomass.
[0007] According to an embodiment of the present application, the iron oxide includes Fe2O3 and optionally a doping element, wherein the doping element includes a rare earth element, and the rare earth element exists in the core in the form of an iron complex.
[0008] According to an embodiment of the present application, the catalyst has a mesoporous structure, and the catalyst satisfies at least one of the following conditions:
[0009] The specific surface area of the catalyst is 140 m 2 / g-220m 2 / g;
[0010] The average pore size of the catalyst is 2-10 nm.
[0011] In another aspect of the present application, the present application proposes a method for preparing the aforementioned catalyst, the method comprising coating an iron-containing oxide with silica microspheres to obtain the catalyst having a core-shell structure, wherein the silica microspheres are in-situ grown on the surface of the iron-containing oxide. The method can obtain the aforementioned catalyst simply and efficiently.
[0012] According to an embodiment of the present application, the method includes:
[0013] The iron-containing inorganic salt and water are uniformly mixed and subjected to a first constant temperature water bath to obtain a solution a;
[0014] Slowly drip a weak acid solution into solution a, place in a second constant temperature water bath, and obtain sol b;
[0015] Add organic solvent and water to the sol b and mix evenly, and place in a third constant temperature water bath to obtain solution c.
[0016] Add the alkaline solution to solution c and perform the fourth constant temperature water bath to obtain solution d
[0017] Slowly dripping the organosilicon solution into the solution d, performing a fifth constant temperature water bath, to obtain a sol e;
[0018] The sol e is dried and calcined to obtain the catalyst.
[0019] According to an embodiment of the present application, the method satisfies at least one of the following conditions:
[0020] The iron-containing inorganic salt includes hydrous ferric nitrate;
[0021] The weak acid solution includes a citric acid solution;
[0022] The organic solvent includes at least one of ethanol and methanol;
[0023] The alkaline solution includes at least one of ammonia water and NaOH;
[0024] The organic silicon solution includes tetraethyl orthosilicate solution.
[0025] According to an embodiment of the present application, the mass ratio of the weak acid in the weak acid solution to the iron-containing inorganic salt is 0.8-1.2.
[0026] According to an embodiment of the present application, the molar ratio of the organic solvent, the alkaline solution, and the organosilicon solution is 1.7-2.4:(0.4-0.6):(0.06-0.16).
[0027] According to an embodiment of the present application, the temperature of the first constant temperature water bath is 75-85°C, and the rotation speed is 300-600r / min; and / or the temperature of the second constant temperature water bath is 75-85°C, and the rotation speed is 600-1200r / min; and / or the temperature of the third constant temperature water bath is 55-65°C, and the rotation speed is 600-1200r / min; and / or the temperature of the fourth constant temperature water bath is 55-65°C, and the rotation speed is 2000-2400r / min; and / or the temperature of the fifth constant temperature water bath is 65-75°C, and the rotation speed is 2000-2400r / min.
[0028] According to the embodiments of the present application, the drying temperature of the sol e is 65-75° C., and the calcination temperature is 45-550° C. for 2-4 hours.
[0029] In another aspect of the present application, the present application proposes the use of the above-mentioned catalyst in the preparation of hydrogen-rich fuel gas by steam gasification of biomass, wherein the volume content of hydrogen in the hydrogen-rich fuel gas is not less than 30%.
[0030] The above summary is for the purpose of description only and is not intended to be limiting in any way. In addition to the illustrative aspects, embodiments and features described above, further aspects, embodiments and features of the present application will be readily apparent through the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 The SEM characterization spectra of the catalysts provided in Examples 1 and 2 of the present application are shown;
[0032] Figure 2 The XRD characterization spectra of the catalysts provided in Examples 1 and 2 of the present application are shown;
[0033] Figure 3 A schematic diagram of a gasification experimental device provided in an embodiment of the present application is shown;
[0034] Figure 4 A bar chart showing various volume fractions and yields of gas phase products obtained during the gasification reaction of Example 3 of the present application;
[0035] Figure 5 The bar chart shows the volume fractions and yields of the gas phase products obtained during the gasification reaction in Example 4 of the present application.
[0036] Figure 6 The volume fractions and yield bar graphs of the gas products obtained during the gasification reaction of Examples 3 and 4 of the present application, the gas products obtained by steam gasification of pure pine wood (PS), and the gas products obtained by traditional dolomite catalyst (DOL) are shown.
[0037] Figure 7 FTIR spectra of the liquid products obtained during the gasification reaction of Examples 3 and 4 of the present application and the liquid products obtained by gasification of pure pine wood (PS) with water vapor DETAILED DESCRIPTION
[0038] In the following, only some exemplary embodiments are briefly described. As those skilled in the art will appreciate, the described embodiments may be modified in various ways without departing from the spirit or scope of the present application, and different embodiments may be combined arbitrarily without conflict. Therefore, the following description is considered to be exemplary and non-restrictive in nature.
[0039] In one aspect of the present application, a catalyst is provided. The catalyst has a core-shell structure, and the core-shell structure includes: a core body, the core body contains iron oxide; a core shell, the core shell covers at least part of the surface of the core body, and the core shell contains silicon dioxide microspheres. The catalyst has the function of catalyzing tar cracking and increasing the volume content of hydrogen in the preparation of hydrogen-rich fuel gas by steam gasification of biomass.
[0040] The catalyst with a core-shell structure proposed in the present application has an iron-containing oxide as a core and a silicon dioxide as a core-shell. When the core-shell catalyst is applied to the catalytic gasification of biomass, it can have the effect of tar cracking and increasing the volume content of hydrogen in the preparation of hydrogen-rich fuel gas by water vapor gasification of biomass. High-temperature pyrolysis of biomass mainly forms wood gas, wood tar, and charcoal. The addition of the catalyst proposed in the present application can promote water gas reaction, methane reforming reaction, promote the catalytic cracking of wood tar to decompose large molecular hydrocarbon substances and large molecular compounds into small molecular compounds and small molecular gases, and promote the oxidation reaction of charcoal to generate gas, thereby increasing the content of hydrogen in the generated fuel gas.
[0041] According to an embodiment of the present application, the iron oxide in the core of the catalyst may include Fe2O3. Fe2O3 has good catalytic activity and can improve the cracking efficiency of tar. In order to further improve the catalytic performance of the catalyst, doping elements may also be performed in the core. For example, the doping elements may include rare earth elements. Those skilled in the art may select appropriate rare earth elements for doping according to the specific biomass selected for biomass gasification hydrogen production and the specific conditions for high-temperature steam gasification hydrogen production. For example, the rare earth element may include at least one of lanthanum, cerium, and praseodymium.
[0042] In one example of the present application, the rare earth element is present in the core in the form of an iron complex. The doping of rare earth elements can optimize the performance of the catalyst, improve the product selectivity and reaction rate of the gasification reaction, improve the thermal stability and service life of the catalyst, and is an important means to improve the performance of the catalyst. The complex can better optimize the electronic structure and redox properties of the catalyst, improve the thermal stability, reaction selectivity and anti-sintering performance of the catalyst. This synergistic effect is an important mechanism for improving the efficiency of the steam gasification reaction, increasing the hydrogen production rate and controlling by-products.
[0043] According to an embodiment of the present application, the catalyst may have a mesoporous structure. Specifically, a catalyst having a mesoporous structure may be obtained by coating with silicon dioxide and controlling the morphology of iron oxide in the core. The mesoporous structure may increase the contact area between the catalyst and the reactant, expose more catalytic active sites, and improve the catalytic efficiency and effect. Specifically, the morphology of the catalyst may satisfy at least one of the following conditions:
[0044] The specific surface area of the catalyst is 140 m 2 / g-220m 2 / g;
[0045] The average pore size of the catalyst is 2-10 nm.
[0046] The catalyst having the above-mentioned microscopic morphology has a better catalytic effect of catalyzing tar cracking and increasing hydrogen production.
[0047] In another aspect of the present application, the present application proposes a method for preparing the aforementioned catalyst. The method comprises coating an iron-containing oxide with silica microspheres to obtain the catalyst having a core-shell structure, wherein the silica microspheres are in-situ grown on the surface of the iron-containing oxide. The method can obtain the aforementioned catalyst simply and efficiently, that is, the aforementioned core-shell structure catalyst can be easily prepared, and has the advantages of simple operation, simplicity and high efficiency, etc.
[0048] On the one hand, the silica microspheres formed by in-situ growth have a stronger contact with the iron-containing oxide, so the catalyst life and the overall integrity of the catalyst after use can be guaranteed. On the other hand, the silica microspheres synthesized in situ are more conducive to the formation of the aforementioned mesoporous structure.
[0049] According to an embodiment of the present application, the method may specifically include the following steps:
[0050] The iron-containing inorganic salt and water are uniformly mixed and subjected to a first constant temperature water bath to obtain a solution a;
[0051] Slowly drip a weak acid solution into solution a, place in a second constant temperature water bath, and obtain sol b;
[0052] Add organic solvent and water to the sol b and mix evenly, and place in a third constant temperature water bath to obtain solution c.
[0053] Add the alkaline solution to solution c and perform the fourth constant temperature water bath to obtain solution d
[0054] Slowly dripping the organosilicon solution into the solution d, performing a fifth constant temperature water bath, to obtain a sol e;
[0055] The sol e is dried and calcined to obtain the catalyst.
[0056] Thus, an iron-containing core precursor can be first formed through a sol process, and then a precursor of silica microspheres can be formed through a sol process using an organic silicon solution, and finally the aforementioned catalyst can be obtained through sintering. The above process is simple to operate on the one hand, and can better control the microscopic morphology of the catalyst on the other hand, so that it has good catalytic performance.
[0057] According to an embodiment of the present application, the method satisfies at least one of the following conditions:
[0058] The iron-containing inorganic salt includes hydrous ferric nitrate;
[0059] The weak acid solution includes a citric acid solution;
[0060] The organic solvent includes at least one of ethanol and methanol;
[0061] The alkaline solution includes at least one of ammonia water and NaOH;
[0062] The organic silicon solution includes tetraethyl orthosilicate solution.
[0063] According to the embodiments of the present application, the mass ratio of the weak acid in the weak acid solution to the iron-containing inorganic salt is 0.8-1.2. As a result, the two can form a more stable complex structure through interactions such as ionic bonds. This reduces the loss of ions due to precipitation or other chemical reactions, allowing them to play a better role. At the same time, new catalytic active sites will be generated, which has a better catalytic effect on certain chemical processes involving redox reactions.
[0064] According to the embodiments of the present application, the molar ratio of the organosilicon in the organic solvent, alkaline solution, and organosilicon solution is 1.7-2.4: (0.4-0.6): (0.06-0.16). As a result, tetraethyl silicate has a high solubility in ethanol, which helps the reaction to proceed in a homogeneous system, promotes the uniformity of the reaction, avoids excessive local concentration leading to a runaway reaction, and enables the reaction to proceed smoothly. This ratio of ammonia water can control the structure and properties of the product silica, and generate silica materials with a certain pore structure, which is very beneficial for catalysis. The amount of tetraethyl silicate used in combination with the amount of other reagents can make the generated silica and other products have good quality and performance. Such an amount is convenient for operation in a laboratory environment, and it is also convenient for optimizing and studying the reaction conditions. For example, in some specific embodiments, the molar ratio of the organosilicon in the organic solvent, alkaline solution, and organosilicon solution can be specifically 1.715mol: 0.43mol: 0.067mol.
[0065] According to an embodiment of the present application, the temperature of the first constant temperature water bath is 75-85°C, and the rotation speed is 300-600r / min; and / or the temperature of the second constant temperature water bath is 75-85°C, and the rotation speed is 600-1200r / min; and / or the temperature of the third constant temperature water bath is 55-65°C, and the rotation speed is 600-1200r / min; and / or the temperature of the fourth constant temperature water bath is 55-65°C, and the rotation speed is 2000-2400r / min; and / or the temperature of the fifth constant temperature water bath is 65-75°C, and the rotation speed is 2000-2400r / min. By adopting the above-mentioned constant temperature water bath conditions, the reactants can be fully mixed and reacted, and by adopting a constant temperature water bath at a higher rotation speed, a catalyst with a mesoporous structure can be obtained.
[0066] According to the embodiments of the present application, the drying temperature of the sol e is 65-75° C., and the calcination temperature is 45-550° C. for 2-4 hours.
[0067] In some embodiments of the present application, the method may specifically include the following steps:
[0068] 1) Evenly mix the iron nitrate with 20 ml of water, and place in a water bath at a constant temperature of 80°C and a speed of 300-600 r / min for 5 minutes;
[0069] 2) uniformly mixing citric acid in an amount twice that of the metal cation with 15 ml of water to obtain a citric acid solution;
[0070] 3) slowly dripping the citric acid solution into the solution obtained in step 1), and placing the solution in a water bath at a temperature of 80° C. and a rotation speed of 600 to 1200 r / min until a gel is formed to obtain an iron oxide sol;
[0071] 4) Add ethanol solution and water (ethanol-water ratio 5:1) to the iron oxide sol and mix evenly, and place in a water bath at a temperature of 60°C and a speed of 300-600r / min for 10 minutes. Slowly drip ammonia water, and place in a water bath at a temperature of 60°C and a speed of 2000-2400r / min for 10 minutes. Slowly drip silicon-containing organic compounds, and place in a water bath at a temperature of 70°C and a speed of 2000-2400r / min until a viscous fluid is formed;
[0072] 5) drying the sample obtained in step 4) in an oven at 70° C. for 12 h;
[0073] 6) The sample of step 5) is placed in a muffle furnace for calcination under the following conditions: heating rate of 10-20°C / min, calcination temperature of 500°C, and calcination time of 3h to obtain a core-shell structure catalyst.
[0074] In another aspect of the present application, the present application proposes the use of the above-mentioned catalyst in the preparation of hydrogen-rich fuel gas by steam gasification of biomass, wherein the volume content of hydrogen in the hydrogen-rich fuel gas is not less than 30%.
[0075] The present invention provides a biomass catalytic gasification method. By adopting the core-shell catalyst, the hydrogen yield can be increased, tar cracking can be promoted, and coke generation can be reduced.
[0076] The method proposed in this application is described below by means of specific examples. The methods used in the following examples are conventional methods unless otherwise specified, and the reagents used are commercially available reagents unless otherwise specified.
[0077] Example 1
[0078] Preparation of catalyst: Evenly mix 6.9073g Fe(NO3)39H2O with 20ml water, and keep it in a constant temperature water bath at 80℃ and 500r / min for 5min. Evenly mix 6.5701g citric acid with 15ml water and slowly drip it into the above solution, and keep it in a constant temperature water bath at 80℃ and 800r / min until a gel is formed to obtain a colloidal iron oxide. Evenly mix 100ml ethanol solution and 20ml water, slowly pour it into the iron oxide and mix it evenly, and keep it in a constant temperature water bath at 60℃ and 500r / min for 10min. Slowly drip 27ml of ammonia water, set the temperature at 60℃, and keep the water bath at 2000r / min for 10min. Slowly drip 15ml of tetraethyl silicate, set the temperature at 70℃, and keep the water bath at 2000r / min until a viscous fluid is formed. Dry the obtained sample in a 70℃ oven for 12h. Put the dried sample into a muffle furnace for calcination. The calcination conditions are: heating rate of 15℃ / min, calcination temperature of 500℃, and calcination time of 3h. 5% Fe2O3@SiO2 is obtained.
[0079] Example 2
[0080] Preparation of catalyst: Evenly mix 12.0238g Fe(NO3)39H2O with 20ml water, and keep it in a constant temperature water bath for 5min in a water bath set at 80℃ and 500r / min. Evenly mix 11.4369g citric acid with 15ml water and slowly drip it into the above solution, and keep it in a constant temperature water bath in a water bath set at 80℃ and 800r / min until a gel is formed to obtain a colloidal iron-containing oxide. Evenly mix 100ml ethanol solution and 20ml water, slowly pour it into the iron-containing oxide and mix it evenly, and keep it in a constant temperature water bath in a water bath set at 60℃ and 500r / min for 10min. Slowly drip 27ml of ammonia water, set the temperature at 60℃, and keep the water bath at 2000r / min for 10min. Slowly drip 15ml of tetraethyl silicate, set the temperature at 70℃, and keep the water bath at 2000r / min until a viscous fluid is formed. Dry the obtained sample in a 70℃ oven for 12h. Put the dried sample into a muffle furnace for calcination. The calcination conditions are: heating rate of 15℃ / min, calcination temperature of 500℃, and calcination time of 3h. 10% Fe2O3@SiO2 is obtained.
[0081] Figure 1 For example 1 (such as Figure 1 a) and 2 (such as Figure 1b) is a SEM photo of the catalyst. The catalyst was analyzed using a dual ion beam field emission scanning electron microscope (F-SEM) of the Czech TESCAN company GAIA 3XMN. It can be seen that Fe2O3@SiO2 is stacked and wrapped with small spheres. The wrapping and superposition of these particles form nanoscale pore channels, which is conducive to providing a higher specific surface area to increase the contact area for the reaction.
[0082] Figure 2 For example 1 (such as Figure 2 a) and 2 (such as Figure 2 In the XRD spectrum of the catalyst in b), the Fe2O3 phase appears at 2θ=24.126°, 33.111°, 35.611°, 40.825° and 49.413°, belonging to the (012), (104), (110), (113) and (024) crystal planes, respectively; the SiO2 phase appears at 2θ=21.022°, 21.136°, 22.927° and 23.247°, belonging to the (123), (200), (211) and (132) crystal planes, respectively.
[0083] Table 1 shows the BET characterization parameters of the catalysts in Examples 1 and 2.
[0084]
[0085] Figure 3 Schematic diagram of gasification experimental device. The device is used to verify the catalytic effect of the catalyst prepared in Examples 1 and 2. The device is mainly composed of a tubular furnace reactor, a water vapor generator, a tar collection and analysis device, and a gas collection and analysis device, and specifically includes a nitrogen bottle 1, a rotor flowmeter 2, a heating device 3, a peristaltic water pump 4, a water reservoir 5, a crucible 6, a temperature control system 7, a condensation system 8, a drying device 9, and a gas collection device 10. The gas generated in the tubular furnace during the reaction is catalyzed by the catalyst in the tubular furnace, and then the reaction products are collected and analyzed. The gas phase product is detected by a 7980A gas chromatograph of Agilent Technologies, USA.
[0086] Example 3
[0087] Gasification application of the catalyst: The tube furnace was heated to 800°C, N2 was introduced at a flow rate of 50 ml / min, and purged for 30 minutes to ensure that the furnace was filled with N2. The tar condensation device and the water vapor absorption device were connected, 3 g of pine wood was weighed and filled into the middle of the quartz boat, and 1.5 g of the catalyst prepared in Example 1 was weighed and filled into the quartz boat for standby use. Water vapor was introduced, and the catalyst and pine wood were placed on both sides of the tube furnace respectively. The pyrolysis reaction was started from the pine wood for 8 minutes, and the products of each phase were collected.
[0088] Figure 4The gas composition analysis results of the gasification reaction of the catalyst prepared in Example 1 showed that the volume fraction of H2 was 34.87%, the volume fraction of CO was 31.57%, the volume fraction of CO2 was 12.24%, and the volume fraction of CH4 was 13.03%. The hydrogen production was 17.5716 mmol / g.
[0089] Example 4
[0090] Gasification application of catalyst: Gasification application of catalyst: Heat the tube furnace to 800°C, introduce N2 at a flow rate of 50 ml / min, purge for 30 min, ensure that the furnace is full of N2, connect the tar condensation device and the water vapor absorption device, weigh 3g of pine wood and fill it in the middle of the quartz boat, weigh 1.5g of the catalyst prepared in Example 2 and fill it in the quartz boat for standby use. Pass water vapor, put the catalyst and pine wood on both sides of the tube furnace respectively, start the pyrolysis reaction from the pine wood for 10 min, and collect the products of each phase.
[0091] Figure 5 The gas composition analysis results of the gasification reaction of the catalyst prepared for Example 2 showed that the volume fraction of H2 was 38.45%, the volume fraction of CO was 22.98%, the volume fraction of CO2 was 22.47%, and the volume fraction of CH4 was 12.09%. The hydrogen production was 19.894 mmol / g.
[0092] Figure 6 The comparison chart of the volume fraction of gas phase products and gas production of pure pine wood gasification (PS), traditional dolomite catalyst (DOL) gasification and Examples 3 (5% Fe2O3@SiO2) and 4 (10% Fe2O3@SiO2) shows that the H2 volume fraction and production of Examples 3 and 4 are significantly improved compared with the H2 volume fraction and production of gasification without catalyst and using traditional catalyst, indicating that the catalysts prepared in Examples 1 and 2 effectively promote the biomass gasification and hydrogen production.
[0093] Figure 7 FTIR spectra of the liquid products of pure pine wood gasification (PS) and Example 3 (5% Fe2O3@SiO2) and 4 (10% Fe2O3@SiO2). -1 In the liquid phase products of Examples 3 and 4, the concentration of such compounds is lower than that of the liquid phase products produced by PS gasification, indicating that alcohol and phenol compounds have been transformed due to the separation of -OH. Aliphatic hydrocarbons lose small molecular groups under the action of catalysts, and the carbon chain skeleton is transformed into aromatics. The liquid phase products of Examples 3 and 4 have a wavelength of 3100-2750cm -1The stretching vibrations of aromatic and aliphatic functional groups corresponding to the olefin terminal double bond, including the antisymmetric stretching vibration frequency of =CH2 on the olefin double bond, the =CH stretching vibration on the olefin double bond, the =CH2 stretching vibration of alkanes, and the =CH3 stretching vibration of alkanes are increased compared with the liquid products produced by PS gasification, indicating that more macromolecular compounds are cracked to form small molecular olefins and alkanes. Among them, the liquid products obtained by 10% Fe2O3@SiO2 gasification are slightly less than those obtained by 5% Fe2O3@SiO2 catalytic gasification, indicating that more volatiles are cracked into gaseous substances, which promotes the CH4 steam reforming reaction. 1670-1520cm -1 The spectral peaks correspond to the stretching vibrations of aromatic C=O and C=C bonds, 1500-1310cm -1 The spectral peaks at 930-650cm correspond to the bending vibration of the alkyl CH functional group and the stretching vibration of the methyl -CH3 functional group. -1 It represents the stretching vibration of the CH functional group in benzene substances, including the peaks near benzene and its derivatives and benzene substitutions, indicating the out-of-plane bending of the aromatic CH bond. The concentration of such compounds in the liquid products of Examples 3 and 4 is significantly reduced compared with the liquid products produced by PS gasification, indicating that under the action of the catalyst, the C=O bond and C=C bond of the aromatic compound and the CH in the benzene substances are broken, producing more small molecular compounds and gases. This shows that the catalysts prepared in Examples 1 and 2 effectively promote the cracking of tar, converting the macromolecular tar into small molecular gases and small molecular hydrocarbon substances.
[0094] It can be seen that the embodiments provided in the present application can have a higher hydrogen yield when applied to the biomass catalytic gasification method for preparing hydrogen-rich fuel gas.
[0095] The above application provides many different embodiments or examples to realize the different structures of the present application. In order to simplify the present application, the parts and settings of specific examples are described above. Of course, they are only examples, and the purpose is not to limit the present application. In addition, the present application can repeat reference numbers and / or reference letters in different examples, and this repetition is for the purpose of simplification and clarity, which itself does not indicate the relationship between the various embodiments and / or settings discussed.
[0096] The above are only specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any technician familiar with the technical field can easily think of various changes or substitutions within the technical scope disclosed in the present application, which should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. A catalyst, characterized in that The catalyst has a core-shell structure, and the core-shell structure comprises: a core body, wherein the core body comprises iron oxide; The core-shell at least covers a portion of the surface of the core body, and the core-shell contains silicon dioxide microspheres.
2. The catalyst according to claim 1, characterized in that The iron oxide comprises Fe2O3, and optionally a doping element, wherein the doping element comprises a rare earth element, The rare earth element exists in the core body in the form of an iron complex.
3. The catalyst according to claim 1 or 2, characterized in that The catalyst has a mesoporous structure, and the catalyst satisfies at least one of the following conditions: The specific surface area of the catalyst is 140 m 2 / g-220m 2 / g; The average pore size of the catalyst is 1-20 nm.
4. A method for preparing the catalyst according to any one of claims 1 to 3, characterized in that: The method comprises coating the iron-containing oxide with silicon dioxide microspheres to obtain the catalyst having a core-shell structure. The silicon dioxide microspheres are in-situ grown on the surface of the iron-containing oxide.
5. The method according to claim 4, characterized in that The method comprises: The iron-containing inorganic salt and water are uniformly mixed and subjected to a first constant temperature water bath to obtain a solution a; Slowly drip a weak acid solution into solution a, place in a second constant temperature water bath, and obtain sol b; Add organic solvent and water to the sol b and mix evenly, and place in a third constant temperature water bath to obtain solution c. Add the alkaline solution to solution c and perform the fourth constant temperature water bath to obtain solution d Slowly dripping the organosilicon solution into the solution d, performing a fifth constant temperature water bath, to obtain a sol e; The sol e is dried and calcined to obtain the catalyst.
6. The method according to claim 5, characterized in that The method satisfies at least one of the following conditions: The iron-containing inorganic salt includes hydrous ferric nitrate; The weak acid solution includes a citric acid solution; The organic solvent includes at least one of ethanol and methanol; The alkaline solution includes at least one of ammonia water and NaOH; The organic silicon solution includes tetraethyl orthosilicate solution.
7. The method according to claim 5 or 6, characterized in that: The mass ratio of the weak acid in the weak acid solution to the iron-containing inorganic salt is 0.8-1.
2. The molar ratio of the organic solvent, the alkaline solution and the organic silicon in the organic silicon solution is 1:(0.27-0.28):(0.15-0.16).
8. The method according to claim 5, characterized in that The temperature of the first constant temperature water bath is 75-85° C., and the rotation speed is 300-600 r / min; and / or The temperature of the second constant temperature water bath is 75-85° C., and the rotation speed is 600-1200 r / min; and / or The temperature of the third constant temperature water bath is 55-65° C., and the rotation speed is 600-1200 r / min; and / or The temperature of the fourth constant temperature water bath is 55-65° C., and the rotation speed is 2000-2400 r / min; and / or The temperature of the fifth constant temperature water bath is 65-75° C., and the rotation speed is 2000-2400 r / min.
9. The method according to claim 5, characterized in that The drying temperature of the sol e is 65-75° C., and the calcination temperature is 45-550° C. for 2-4 hours.
10. Use of the catalyst according to any one of claims 1 to 3 in preparing hydrogen-rich fuel gas by steam gasification of biomass, The volume content of hydrogen in the hydrogen-rich fuel gas is not less than 30%.